THE EFFECTIVENESS OF THE DRILL METHOD IN INCREASING ELEMENTARY SCHOOL STUDENTS' SHOOTING ACCURACY ABILITY - Fauzan, Fauzan; Hasibuan, Afrina Yanti (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
This study aims to determine the problems of fourth grade teachers in implementing the 2013 curriculum at SDN 081 Panyabungan. This study uses a qualitative descriptive method. Data collection and processing techniques use observation, interviews, and documentation. The procedure for collecting and processing data passes through 3 stages, namely the preparation stage, the implementation stage, and the final stage. Data analysis techniques are data reduction, data display/data presentation, and conclusion drawing. The results of this study indicate that the data obtained from the results of the lesson plans and the assessment of teaching practice in implementing the 2013 curriculum at SDN 081 Panyabungan are included in the good category. With a total average value for the results of the RPP assessment is 87.75 and the assessment of teaching practice is 86.37. l From these data it can be said that the implementation of the 2013 curriculum in grade IV elementary schools is in the good category